Carbon content and climate variability drive global soil bacterial diversity patterns. Issue 3 (1st August 2016) - Delgado‐Baquerizo, Manuel; Maestre, Fernando T.; Reich, Peter B.; Trivedi, Pankaj; Osanai, Yui; Liu, Yu‐Rong; Hamonts, Kelly; Jeffries, Thomas C.; Singh, Brajesh K.
Abstract: Despite the vital role of microorganisms for ecosystem functioning and human welfare, our understanding of their global diversity and biogeographical patterns lags significantly behind that of plants and animals. We conducted a meta‐analysis including ~600 soil samples from all continents to evaluate the biogeographical patterns and drivers of bacterial diversity in terrestrial ecosystems at the global scale. Similar to what has been found with plants and animals, the diversity of soil bacteria in the Southern Hemisphere decreased from the equator to Antarctica. However, soil bacteria showed similar levels of diversity across the Northern Hemisphere. The composition of bacterial communities followed dissimilar patterns between hemispheres, as the Southern and Northern Hemispheres were dominated by Actinobacteria and Acidobacteria, respectively. However, Proteobacteria was co‐dominant in both hemispheres. Moreover, we found a decrease in soil bacterial diversity with altitude. Climatic features (e.g., high diurnal temperature range and low temperature) were correlated with the lower diversity found at high elevations, but geographical gradients in soil total carbon and species turnover were important drivers of the observed latitudinal patterns. We thus found both parallels and differences in the biogeographical patterns of aboveground vs. soil bacterial diversity. Our findings support previous studies that highlighted soil pH, spatial influence, and organic matter as important drivers of bacterial diversity and composition. Furthermore, our results provide a novel integrative view of how climate and soil factors influence soil bacterial diversity at the global scale, which is critical to improve ecosystem and earth system simulation models and for formulating sustainable ecosystem management and conservation policies.